The reformed EU ETS in times of economic crises: The case of the COVID-19 pandemic - Johanna Bocklet (Institute of Energy Economics at the University of Cologne (EWI), 2020)
To tackle structural supply-demand imbalances and to increase price stability in times of economic crises,policy makers reformed the European Union Emission Trading System (EU ETS) substantially in 2015 and 2018. As the COVID-19 pandemic led to an unforeseen contraction of the economy,it serves as an example to evaluate if the reforms can live up these goals. The paper at hand uses a partial equilibrium model that depicts current EU ETS regulation to determine the impact of the pandemic on allowance prices and emissions the EU ETS.The results indicate that due to the Market Stability Reserve (MSR) and the Cancellation Mechanism, the Corona crisis reduces aggregate emissions in the EU ETS. This finding holds even if the crisis is followed by an economic rebound in the same or larger magnitude than the initial recession. Further, the new regulation increases the robustness of the ETS towards economic shocks as the reforms increase the relative price stability in the market. While these findings hold for the COVID-19 pandemic, the results can yet not be generalized to a generic economic crisis since they strongly depend on the shape, size and timing of the exogenous shock.
Keywords: D25; D91; H32; Q58; 330; Dynamic Optimization; EU ETS; COVID-19; Market Stability Reserve; Economic Shock